A Decision Support Tool for Water Supply System Decentralization via Distribution Network Sectorization - Vegas Niño, Oscar T.; Martínez Alzamora, Fernando; Tzatchkov, Velitchko G. (Processes, 2021)
Many water supply systems, conceived to operate in centralized manner, face difficulties to adapt to dynamic changes, such as population growth, city extension, and industrial development. Decentralization of these systems may be an effective solution. Known techniques for distribution network sectorization design can help to achieve such a goal, but this has not been recognized in the literature. None of those known techniques considers the conversion of a centralized system to a decentralized one. In this paper, two new distinct yet complementary methodologies for water supply system decentralization by distribution network sectorization are proposed and implemented in a software decision support tool freely available on internet. The first methodology identifies the main flow paths from water sources to some strategic nodes and considers the nodes in these paths as new potential sources for dividing the rest of the network. The second methodology sectorizes the network according to the contribution of sources to the consumption at nodes, based on mass balance equations for the transport of a hypothetical conservative constituent in a steady state. Both methods were applied to two real network models. The results obtained were better, for decentralizing the supply, compared to those obtained by other methodologies proposed in the literature.